Evaluation of CROPGRO-Tomato Model under Different Dates of Planting and Cultivars under Semi-arid Environment - Shravika, L.; Sreenivas, G.; Madhavi, A.; Rao, A. Manohar (International Journal of Bio-resource and Stress Management, 2021)
A field investigation was undertaken during Kharif (June–September)2019 at Agriculture Research Institute, Professor Jayashankar Telangana State Agriculture University, Rajendranagar, Hyderabad, Telengana State, India with an object to evaluate the CROPGRO-Tomato model under different dates of planting and cultivars.The experiment was carried out with dates of planting (02nd Jul, 12th Jul, 22nd Jul, 02nd Aug, 11th Aug, 23rd Aug, 03rd Sep and 13th Sep) as main plot treatments and cultivars US 440 and TO-3251 (Saaho) as sub-plot treatments. The CROPGRO-Tomato model performed well in the simulation of phenology, biomass, fruit yield and N uptake during calibration for US 440 and TO-3251.Calibration results revealed that the model perfectly predicted days to anthesis with no difference between simulated and observed data for both cultivars with RMSE of 0 days, the further model simulated the days to last picking,biomassat maturity, fruit yield and nitrogen uptake with RMSE of 0.9 and 0.7 day, 285 and 435 kg ha-1, 545 kg ha-1 and 389 kg ha-1 (dry weight), 6 and 5 kg ha-1 for US 440 and TO-3251 cultivars respectively. The calibrated model was used to further validate the experimental data and found that, simulation of days to anthesisand days to the last picking was excellent with NRMSE value of less than 10% for both cultivars,fair with dry matter production with NRMSE value of 25% for both cultivars and was poor with total fruit yield greater than 30% and N uptake for both cultivars under study was poor with NRMSE value more than 30%